Congenital granula cell tumour: report of a case - M. Emmanuel; A. C. Olojede; A. A. Kusamotu; O. M. Gbotolorun; W. L. Adeyemo (Nigerian Dental Association, 2009)
Congenital granular cell tumour of the newborn is an uncommon benign tumour of uncertain origin. Mostly, it occurs as a single tumour but rarely as multiple. The lesion arises from the mucosa of the gingiva either from maxillary or mandibular alveolar ridge. This paper reports a three-day old female patient who presented at the dental centre of General Hospital, Lagos with a pedunculated soft tissue mass arising from the incisal region of the maxillary alveolar ridge. The lesion was excised under local anasthaesia when the baby was four days old. Microscopic examination of the lesion showed stratified squamous epithelium overlying sheets of large polygonal cells with granular cytoplasm and a diagnosis was congenital granular cell tumour. In view of the fact that cases reported in the scientific literature are not too many, there is justification for report of this case and reports of more cases are recommended.